Esketamine has no effect on cognition compared to midazolam - Alison Knopf (The Brown University Child & Adolescent Psychopharmacology Update, 2023)
Little is known about the effect of ketamine, which has a rapid and robust effect on depressive symptoms and suicidal ideation, on cognition in adolescents. Researchers in China conducted a randomized controlled trial on 51 participants 13–18 years old with major depression disorder (MDD) and suicidal ideation. The participants received esketamine or midazolam in three intravenous infusions. Processing speed, working memory, verbal learning, and visual learning were assessed at days 0, 6, and 12. The researchers found that cognition was not harmed by the esketamine, and in fact esketamine improved processing speed. [Lan, X., Wang, C., Zhang, F., et al. (2023, Sep 14). Short‐term cognitive effects of repeated‐dose esketamine in adolescents with major depressive disorder and suicidal ideation: A randomized controlled trial. Child Adolesc Psychiatry Ment Health , 17 (1), 108. http://doi.org/10.1186/s13034‐023‐00647‐2 .]